2015
DOI: 10.1007/s11596-015-1445-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, social support and medication adherence in patients with ischemic stroke in the mainland of China

Abstract: Stroke research and rehabilitation have traditionally focused on the physical and functional impact of a stroke. Less attention has been given to the psychosocial factors associated with this chronic condition. By the few studies that have specifically focused on psychosocial factors in the context of stroke, poststroke depression is demonstrated to significantly influence stroke outcomes. Associations of stroke with psychological symptoms other than depression have rarely been evaluated. This study was aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…Conversely, living alone and the lack of family support have been associated with lower compliance in several investigations. 26,33 Surprisingly, lower educational level was associated with improved adherence among in the present study. Other studies showed contrasting outcomes, such as in Nigeria, where stroke survivors with a tertiary educational level were 48 time more likely to be knowledgeable about stroke and more compliant to treatment than those with lower education.…”
Section: Methods Design and Settingcontrasting
confidence: 56%
“…Conversely, living alone and the lack of family support have been associated with lower compliance in several investigations. 26,33 Surprisingly, lower educational level was associated with improved adherence among in the present study. Other studies showed contrasting outcomes, such as in Nigeria, where stroke survivors with a tertiary educational level were 48 time more likely to be knowledgeable about stroke and more compliant to treatment than those with lower education.…”
Section: Methods Design and Settingcontrasting
confidence: 56%
“…The selection criteria for cerebral infarction were based on the diagnostic code drafted at the Fourth Cerebral Vascular Disease Academic Conference in 1995, coupled with confirmation by cranial CT scan or MRI [3-5]. Exclusion criteria included transient ischemia attack, cerebral hemorrhage on admission or hemorrhage secondary to ischemic stroke, reversible ischemic neurologic deficit, ischemic stroke with an absence of symptoms, criteria consistent with ischemic stroke, but without sufficient clinical data.…”
Section: Methodsmentioning
confidence: 99%
“…Effective management including modern western medicine with one or more types of Chinese herb medicine was used, and physical rehabilitation was carried out after admission [1, 3-5]. Routine medications for all ischemic stroke patients in both groups included anti-platelet agents, antihypertensive, hypoglycemic and anti-hyperlipidemic drugs, as well as water-salt electrolyte formulations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations